The Biblical Views of Divorce According to Matthew 19:3–9. - Philiam Alaku (Uganda Christian University, 2024)
The study explored various academic interpretations and perspectives on marriage and divorce. It investigated into the historical, theological, and sociocultural contexts that shaped these perspectives. By examining the works of theologians, biblical scholars, and historians, the research aimed to provide a comprehensive understanding of how marriage and divorce have been viewed and interpreted within the Christian tradition. This scholarly discussion highlighted the evolution of thought on these topics and how they aligned or diverged from the teachings found in Matthew 19:3-9. To Investigate Ways through which the Church Can Respond to Issues of Divorce that Arise in Families and Churches: The research focused on developing practical and pastoral strategies for the church to effectively address and manage divorce-related issues within its congregations and among its members. It considered current challenges faced by families and individuals experiencing divorce, and proposed ways the church could offer support, guidance, and healing. This included examining existing church practices and pastoral care models, as well as suggesting new approaches that were both theologically sound and pastorally sensitive. Through a thorough exegesis of Matthew 19:3-9 and a review of scholarly literature, this study sought to contribute to a deeper understanding of marriage and divorce in Christian theology. The exegesis involved a detailed analysis of the biblical text, considering its historical and literary context, and interpreting its meaning for contemporary believers. The review of scholarly literature provided a broad overview of the various interpretations and debates surrounding marriage and divorce in the Christian tradition. Ultimately, this research aimed to provide actionable insights for church leaders and practitioners in supporting families and individuals facing the challenges of divorce. By integrating biblical exegesis with scholarly perspectives and practical recommendations, the study hoped to offer a holistic approach to addressing divorce within the church. This research was submitted in partial fulfillment of the requirements for the award of a Bachelor's degree at Uganda Christian University
Undergraduate Research
Keywords: Biblical Views; Divorce; Matthew